Implementation of E-Commerce and Content in the Kopi Pilah MSME in Pematang Village - Lilyana, Besti; Anwar, Mashuril (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Pematang Village, located in Kalianda District, South Lampung Regency, possesses significant local economic potential, particularly in the agricultural and plantation sectors. One of its leading potentials lies in small and medium enterprises (SMEs) engaged in coffee production, managed by the local community. Kopi Pilah Green Bean, owned by Mr. Rido, is one such SME focusing on processing green coffee beans sourced from local harvests. Despite offering quality products, the enterprise faces challenges in digital marketing, promotional content creation, and the utilization of e-commerce platforms to expand its market reach. This community service activity was carried out through a mentoring approach and the implementation of business digitalization strategies, including the creation of attractive promotional content, optimization of social media, and integration of products into relevant e-commerce platforms. Additionally, training was conducted on the use of design and word-processing applications, as well as assistance in developing a digital business profile connected to Google Maps and online marketplaces. The results of the activity showed an increase in customer engagement, market reach, and product sales. The SME also began to understand the basics of using digital media and implementing non-cash transactions through the QRIS system. Other positive impacts included improved community digital literacy and the strengthening of Pematang Village’s image as an independent and innovative village. Thus, this activity contributes significantly to enhancing the competitiveness of local SMEs through sustainable digital transformation.